SOSIALISASI CYBER SECURITY TERHADAP KEAMANAN DATA PRIBADI DI ERA DIGITAL PADA MTS AL HIDAYAH GUNUNG SINDUR - A.Nurul Anwar; Saprudin; Dani (Abdi Jurnal Publikasi, 2025)
In the digital era, individuals' personal data is increasingly vulnerable to potential misuse and privacy violations. In the process, personal data becomes increasingly important and sensitive because many MTs Alhidayah students carry out online activities. Personal data includes information such as name, address, identification number, financial information, medical history and other sensitive information relating to an individual. Nowadays, almost all devices are connected and have an internet connection, everything can be managed from anywhere. So individual personal data is increasingly vulnerable to potential misuse and privacy violations. One of them is the security aspect in the form of cyber crime threats. Therefore, cyber security has a vital role in preventing cyber crime. Currently, MTs Alhidayah students use gadgets as part of their daily activities, but they still lack knowledge about data security. The aim of this community service is to obtain an overview of cyber security and its challenges in the future, so that students have awareness of the importance of protecting personal data to prevent misuse of data by irresponsible people.